2006
DOI: 10.1128/jcm.01308-06
|View full text |Cite
|
Sign up to set email alerts
|

First Case of Staphylococcus pseudintermedius Infection in a Human

Abstract: We present the first clinical report of a Staphylococcus pseudintermedius infection in a human. Biochemically, S. pseudintermedius can be easily misidentified as S. aureus. Therefore, the final microbiological identification requires the combination of phenotypic and genotypic tests. CASE REPORTA 60-year-old male patient was referred to our center because of ischemic cardiomyopathy and ventricle tachycardia, for which he had received an implantable cardioverter-defibrillator (ICD) in January 2004. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
117
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(126 citation statements)
references
References 7 publications
5
117
0
4
Order By: Relevance
“…The isolates exhibited positive PCR-restriction fragment length polymorphism of the 320-bp fragment in the pta gene, which was compatible with the identification of S. pseudintermedius (1). These isolates were resistant to polymyxin E (10-g colistin disk) by the disk diffusion method, which was also in accordance with the identification of S. pseudintermedius (6). The MICs of these isolates to penicillin, oxacillin, ciprofloxacin, and vancomycin had identical values of Ͼ0.25 g/ml, Յ0.25 g/ml, Յ0.25 g/ml, and Յ1 g/ml, respectively, as determined by the Phoenix automated system.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…The isolates exhibited positive PCR-restriction fragment length polymorphism of the 320-bp fragment in the pta gene, which was compatible with the identification of S. pseudintermedius (1). These isolates were resistant to polymyxin E (10-g colistin disk) by the disk diffusion method, which was also in accordance with the identification of S. pseudintermedius (6). The MICs of these isolates to penicillin, oxacillin, ciprofloxacin, and vancomycin had identical values of Ͼ0.25 g/ml, Յ0.25 g/ml, Յ0.25 g/ml, and Յ1 g/ml, respectively, as determined by the Phoenix automated system.…”
supporting
confidence: 77%
“…S. pseudintermedius is one of the most common pathogens isolated from skin and ear infections in dogs (3)(4)(5). Van Hoovels et al (6) reported the first case of S. pseudintermedius human infection in 2006. This pathogen was isolated from an infected implantable cardioverter defibrillator from a patient without animal contact history (6).…”
mentioning
confidence: 99%
“…18 Staphylococcus pseudintermedius is occasionally isolated from humans, and zoonotic transfer from dogs has been implicated. 6,12,22,23 There are currently no recommendations for interpretation of oxacillin susceptibility tests performed on human isolates of coagulase-positive staphylococci other than S. aureus. 8 However, the Clinical and Laboratory Standards Institute (CLSI; formerly National Committee for Clinical Laboratory Standards) recently recommended that oxacillin susceptibility of S. pseudintermedius and other veterinary isolates of coagulase-positive staphylococci be determined using breakpoints equivalent to those recommended for human and veterinary isolates of S. aureus.…”
Section: Introductionmentioning
confidence: 99%
“…Transmission of pathogenic staphylococci may occur between pets and owners. There have been several recent reports describing the carriage of indistinguishable coagulase-positive staphylococci strains in humans and animals (Van Hoovels et al 2006;Hanselman et al 2009). …”
mentioning
confidence: 99%